Bridging the technological divide technology adoption by firms in developing countries - Cirera, Xavier (World Bank Publications, 2022)
Front Cover -- Contents -- Foreword -- Preface -- Acknowledgments -- About the Authors -- Abbreviations -- Introduction -- The Imperative of Technology in Developing Countries -- The Technological Divide -- Road Map to the Volume -- Contributions to the Literature -- Main Messages from the Volume -- Notes -- References -- Part 1 Measuring the Technological Divide -- 1. A New Approach to Measure Technology Adoption by Firms -- Introduction -- Measuring Adoption and Use of Technology by Firms -- Opening the Black Box: The Firm-level Adoption of Technology (FAT) Survey -- The Data Used in This Volume -- Using the FAT Data to Understand Some of the Limitations of Standard Measures of Technology -- Summing Up -- Notes -- References -- 2. Facts about Technology Adoption and Use in Developing Countries -- Introduction -- Cross-Country Technology Facts -- Cross-Firm Technology Facts -- Other Technology Facts -- Summing Up -- Notes -- References -- 3. Adoption of Sector-Specific Technologies -- Introduction -- Technology Differences across and within Sectors -- Technology Upgrading and the Limits to Leapfrogging -- Specialization, Technology, and Outsourcing -- Summing Up -- Notes -- References -- Part 2 The Implications of the Technological Divide for Long-Term Economic Growth -- 4. Technology Sophistication, Productivity, and Employment -- Introduction -- Technology and Firm-Level Productivity -- Technology Adoption and Employment -- Summing Up -- Notes -- References -- 5. Digital Technologies and Resilience to Shocks -- Introduction -- Digital Technologies -- Technology and Resilience -- Summing Up -- Notes -- References -- Part 3 What Countries Can Do to Bridge the Technological Divide -- 6. What Constrains Firms from Adopting Better Technologies? -- Introduction -- Firm-Level Determinants of Adoption.
Keywords: Electronic books